Deciphering signet ring cells in the bone marrow of a child – a rare case report with review of literature - Mili Jain; Anurag Singh; Preeti Agarwal; Nishant Verma (Polish Journal of Pathology)
The metastatic gastric adenocarcinoma that diffusely invades the bone marrow frequently has a short clinical course and an unfavourable prognosis. This case study aimed to elucidate the clinicopathological characteristics and prognosis of gastric cancer patients with diffuse bone marrow metastases. The specific clinicopathologic features associated with diffuse bone metastasis from gastric cancer must be given special attention due to the poor prognosis of this condition. Regular follow-up and a bone marrow examination in high-risk patients can assist in identifying advanced disease early.